Health-Related Physical Fitness and Arterial Stiffness in Childhood Cancer Survivors - von Korn, Pia; Müller, Jan; Quell, Christina; Tenius, Lisa; Oberhoffer, Renate; Feuchtinger, Tobias; Schmid, Irene (Frontiers in Cardiovascular Medicine, 2019)
Introduction: Despite decreasing mortality in pediatric oncology as a result of standardized treatment protocols, the high number of functional and cardiovascular late sequelae due to anticarcinogenic therapy remains unchanged. The aim of this study was to further assess functional limitations in Health-related Physical Fitness (HRPF) and cardiovascular risk by means of markers of arterial stiffness in Childhood Cancer Survivors (CCS). Materials and Methods: Between March 2016 to August 2017 a total of 92 CCS (Age 12.5 ± 4.2 years, 43 girls) were recruited from their routine follow-up outpatient visit. HRPF was assessed using five Fitnessgram® tasks. Pulse Wave Velocity (PWV) along with peripheral and central blood pressure were assessed using oscillometric measurements performed by Mobil-O-Graph. Z-scores were used to compare the test results either to German reference values or to a recent healthy reference cohort. Results: In CCS, the HRPF was significantly reduced (z-score: -0.28 ± 1.01, p=.011) as compared to healthy peers. The peripheral Systolic Blood Pressure (pSBP) was significantly increased (z-score: 0.31 ± 1.11, p=.017) and the peripheral Diastolic Blood Pressure (pDBP) was decreased (z-score: -0.30 ± 1.25, p=.040), resulting in an inscreased pulse pressure. The PWV (p=.649) and cSBP (p=.408), were neither increased nor showed any association to HRPF. Discussion: CCS showed functional limitations in HRPF and an increased pulse pressure, which acts as an early onset parameter of arterial stiffness. Both a low HRPF and impaired hemodynamics are independent cardiovascular risk factors and needs to be taken into consideration in tertiary prevention of CCS.